2020
DOI: 10.1186/s40644-020-00319-w
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up schedule for initial recurrent hepatocellular carcinoma after ablation based on risk classification

Abstract: Background: To date, no standard follow-up guidelines exist regarding patients receiving ablation for initial recurrent hepatocellular carcinoma (HCC). We aimed to explore whether intensive follow-up could benefit these patients. Methods: We reviewed the clinical data of patients who received complete ablation for initial HCC recurrence after curative treatments in our institution from January 2005 to June 2017. Risk factors for second recurrence of HCC were identified by univariate and multivariate analyses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Liu et al [ 37 ] found that the overall survival of the short-interval group (<4 months) was better than that of the long-interval group (4–6 months) for HCC patients with multiple tumors less than 3 cm or a solitary tumor between 3 and 5 cm following curative thermal ablation. In contrast, the intensive interval for follow-up visits has not been shown to prolong overall survival as reported in two recent studies [ 38 , 39 ]. However, costs of follow-up were not taken into account in these prior studies.…”
Section: Discussionmentioning
confidence: 92%
“…Liu et al [ 37 ] found that the overall survival of the short-interval group (<4 months) was better than that of the long-interval group (4–6 months) for HCC patients with multiple tumors less than 3 cm or a solitary tumor between 3 and 5 cm following curative thermal ablation. In contrast, the intensive interval for follow-up visits has not been shown to prolong overall survival as reported in two recent studies [ 38 , 39 ]. However, costs of follow-up were not taken into account in these prior studies.…”
Section: Discussionmentioning
confidence: 92%
“…LTP is considered related to the microscopic spread of residual tumor cells beyond the ablation margin and the local environment of a tumor (e.g., contact with blood vessels). In contrast, intrahepatic and extrahepatic metastases tend to depend on the aggressiveness and biological behavior of each tumor itself [ 23 25 ]. This fact explains the low sensitivity of MAM in predicting overall early recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…However, more than half of the recurrences developed within 1 year and up to one third within 6 months 25 . Data appear to be similar for thermal ablation 26 . Per current guidelines, the recommended follow‐up regimen consists in contrast‐enhanced sectional imaging every 3 months for the first year 27,28 .…”
Section: Hepatitis C Virus and Early Hepatocellular Carcinoma—best Timing Of Treatmentmentioning
confidence: 97%
“…Given that no data is currently available with regards to the best timing for HCV treatment, a sensitive approach would be to start the DAAs regimen when the certainty for cancer control is maximal, and this moment appears to be in the 3–6 months range. Moreover, while choosing the optimum starting point, one might take into account previously described risk factors for recurrence, such as BCLC stage (0 vs A), tumor size, location, and the extent of vascular invasion in the resection specimen for patients who benefited from surgery 26 …”
Section: Hepatitis C Virus and Early Hepatocellular Carcinoma—best Timing Of Treatmentmentioning
confidence: 99%